The Eurasian Dry Grassland Group (EDGG) in 2018–2019 - Dengler, Jürgen; Aleksanyan, Alla; Ambarlı, Didem; Biurrun, Idoia; Dembicz, Iwona; Kuzemko, Anna; Török, Péter; Venn, Stephen; Vrahnakis, Michael (Hacquetia, 2025)
This report summarises the activities and achievements of the Eurasian Dry Grassland Group (EDGG) from January 2018 through July 2019. During the reported period, two Eurasian Grassland Conference (EGCs) took place: the 15th EGC in Sulmona, Italy, and the 16th EGC in Graz, Austria. The 11th and 12th EDGG Field Workshops studied vegetation diversity patterns in the inner alpine valleys of Austria and Switzerland, while the 13th Field Workshop was organised in Armenia. The formerly electronic newsletter of EDGG (Bulletin of the Eurasian Dry Grassland) was transformed into a peer-reviewed international journal, called Palaearctic Grasslands, which now is attracting both scientific and photographic contributions. Furthermore, the EDGG homepage was re-constructed with a new design and content management system. The EDGG has also finalised two grassland-related Special Features during the past 1.5 years in the international journals Tuexenia and Hacquetia, and contributed with eight chapters to the book Grasslands of the World: Diversity, Management and Conservation. The vegetation plot database GrassPlot, containing standardised multi-scale data from Palaearctic grasslands and closely connected with EDGG, has developed well, as did some other regional and national grassland-focused databases.